2013
DOI: 10.1021/ja407749w
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Allene Hydrosilylation Catalyzed by N-Heterocyclic Carbene Complexes of Nickel and Palladium

Abstract: Regioselective methods for allene hydrosilylation have been developed, with regioselectivity being governed primarily by choice of metal. Alkenylsilanes are produced via nickel catalysis with larger N-heterocyclic carbene ligands, and allylsilanes are produced via palladium catalysis with smaller N-heterocyclic carbene ligands. These complementary methods allow either regioisomeric product to be obtained with exceptional regiocontrol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 51 publications
4
57
0
Order By: Relevance
“…On the other hand, scenarios where directing groups are not easily installed or removed present a different set of challenges and require the development of non-directed approaches. 1,6-10 In these cases involving non-directed additions, π-components in regioselective and regiodivergent processes can typically be classified as biased or unbiased as illustrated for alkenes, alkynes, and allenes (Scheme 2). With biased substrates such as monosubstituted π-systems 1a-c , or alternatively disubstituted π-systems 2a-c where R 1 and R 2 markedly differ in steric or electronic properties, structural features of the substrates influence the properties of the π-system.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, scenarios where directing groups are not easily installed or removed present a different set of challenges and require the development of non-directed approaches. 1,6-10 In these cases involving non-directed additions, π-components in regioselective and regiodivergent processes can typically be classified as biased or unbiased as illustrated for alkenes, alkynes, and allenes (Scheme 2). With biased substrates such as monosubstituted π-systems 1a-c , or alternatively disubstituted π-systems 2a-c where R 1 and R 2 markedly differ in steric or electronic properties, structural features of the substrates influence the properties of the π-system.…”
Section: Introductionmentioning
confidence: 99%
“…Montgomery and co‐workers reported that vinylsilanes could be accessed with Pd(0) NHC catalysts (Figure , L1 ) . They also established the classic N‐heterocyclic carbene complexes of Pd(0) catalyst system (Figure , L2 ) for branched allylsilanes. Another method for branched allylsilanes was developed by Schmidt et al.…”
Section: Figurementioning
confidence: 95%
“…Hence, the development of new and efficient methods for the synthesis of versatile allylsilanes has been paid more and more attention. The hydrosilylation of allenes is one of the most straightforward and atom‐economical approaches to prepare such compound, which has been achieved with various metal catalysts, such as Mo, Co, Ni, Pd and Au . However, controling the regio‐ and stereoselectivity is still challenging in this reaction, as up to six potential isomeric products can be generated (Figure a).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Montgomery and co‐workers reported the regioselective hydrosilylation of allenes catalyzed by Ni 0 and Pd 0 catalysts in the presence of an NHC ligand (Scheme ). Interestingly, vinylsilanes are the major products when a Ni catalyst is used in the presence of a bulky NHC ligand, whereas allylsilanes are the major products by using Pd catalysts in the presence of small NHC ligands.…”
Section: Ni‐catalyzed Hydrofunctionalization (H−x)mentioning
confidence: 99%